The Effect of Problem Based Learning Model on Critical Thinking Ability Student Mathematics and Adversity Student Quotient on Students SMP Negeri 4 Lubukpakam - Saut Lamhot Sitanggang; Edi Syahputra; Anita Yus (BIRCU, 2020)
This study aims to determine the effect of the Problem-Based Learning model on students' mathematical critical thinking skills and Adversity Quotient. In addition, this study was also to see the interaction between learning and gender on students' mathematical critical thinking skills and Adversity Quotient. This research is a quasi-experimental research. The population in this study were all students at SMP N 4 LubukPakam for the 2020/2021 academic year, totaling 384 students. The research sample was 60 students, namely 30 students in class VII-1 and 30 students in class VII-2. The sample was selected by cluster random sampling. The instruments used were the mathematical critical thinking ability test and the Adversity Quotient attitude scale. The data obtained were analyzed using ANAVA in the Spss 20 program. The results showed that: 1) there was an effect of the Problem-Based Learning model on students' mathematical critical thinking skills with a significance value of 0.001 <0.05. 2) there is an effect of the Problem-Based Learning model on students' Adversity Quotient with a significance value of 0.00 <0.05. 3) there is no interaction between learning and gender on students' mathematical critical thinking skills with a significance value of 0.750> 0.05. 4) there is an interaction between learning and gender on students' Adversity Quotient with a significance value of 0.013 <0.05.